Assessment the impact of operator experience on cyclic fatigue resistance in reciprocating and rotary NiTi files: a comparative study between dental students and pediatric dentistry specialists - Özyürek, Hande; Elbay, Mesut; Özyürek, Taha (Frontiers in Materials, 2023)
Introduction: Devices reducing clinical practice time, and which get minimally affected by user experience are invaluable in pediatric dentistry. Additionally, knowing the fracture resistance of different nickel-titanium (NiTi) files for root canal preparation of primary teeth is important for treatment success. Thus, the present study aimed to compare the instrumentation time (IT) and fracture resistance of reciprocating T-endo MUST (TEM) and continuously rotating AF Baby File (ABF) NiTi files according to the use of pediatric dentistry specialists. Methods: According to their clinical experience level, 3 experimental groups (EG)s were formed namely: no experience, 2-years (less-experienced), and 10-years experienced pediatric dentistry specialists' groups. The fourth group was the control group (CG). In each EGs, 10 TEM (25/.06) and 10 ABF 20/.04, and 10 ABF 25/.04 NiTi file systems were used in 20 artificial resin teeth. Instrumentation time was recorded for each tooth. In the CG, the same number of files were not used for instrumentation. The files in all groups were subjected to a dynamic cyclic fatigue test, and the data were analyzed using the Kruskal–Wallis test at 5% significance level. Results: In all groups, TEM files showed a significant higher fatigue resistance as compared to ABF files. However, fatigue resistances were significantly lower in (EG)s both in TEM and ABF compared to (CG)s. The instrumentation time was found to be significantly lower in TEM compared to the ABF. Also, for both file systems, the experience level did not affect the fatigue resistance, and instrumentation time. Discussion: The experience level of the pediatric dentist did not affect the cyclic fatigue resistance of the reciprocating and rotating NiTi files, but the instrumentation time was lower for the reciprocating NiTi files.